Modeling predicts facile release of nitrite but not nitric oxide from the thionitrate CH3SNO2 with relevance to nitroglycerin bioactivation - Vinod Parmar; Esam A. Orabi; Ann M. English; Gilles H. Peslherbe (Scientific Reports)
Abstract Nitroglycerin is a potent vasodilator in clinical use since the late 1800s. It functions as a prodrug that is bioactivated by formation of an enzyme-based thionitrate, E–Cys–NO2. This intermediate reportedly decomposes to release NO and NO2 − but their relative yields remain controversial. Hence, we determined barriers for NO and NO2 − production from the model thionitrate, CH3SNO2, using comprehensive high-level quantum chemistry calculations [CCSD(T)//MP2/aug-cc-pVTZ]. We find that the sulfenyl nitrite, CH3SONO, readily releases NO on (S)O–N bond homolysis but CH3SONO formation from CH3SNO2 either by S–NO2 bond homolysis or concerted rearrangement faces prohibitively high barriers (ΔH calc/ΔH ‡ calc > 42 kcal/mol). Dramatically lower barriers (ΔH ‡ calc ~ 17–21 kcal/mol) control NO2 − release from CH3SNO2 by gas-phase hydrolysis or nucleophilic attack by OH− or CH3S− on the sulfur atom within the C–S–NO2 molecular plane. Moreover, attack by either anion along the S–NO2 bond results in barrierless NO2 − release (ΔH ‡ calc ~ 0 kcal/mol) since a σ-hole (i.e., area of positive electrostatic potential) extends from this bond. Consistent with our high-level calculations, ALDH2 and GAPDH, enzymes implicated in nitroglycerin bioactivation via an E–Cys–NO2 intermediate, catalyze mainly or exclusively NO2 − release from the prodrug.